Regions on a global platform - Mohd Shukri Hajinoor,; Rahmah Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2007)
The theme "Regions on a Global Platform" seeks to deliberate and synthesise on the conceptualisation, roles, and positions of "regions" amid the globalising forces. It suggests that "regionsJ' are not less, but on the other hand are becoming more important with the advent of globalisation as regions may play the balancing role between the global forces and local reactions/pro-activeness. Economic globalisation in particular tends to link local innovative and productive centres around the globe through trade and investment. However, this paper posits that developments on this global-local nexus lead toward regionalisation of the locale with its wider region due to the logic of a complex system of spatial nodes and nehvorks offirms, suppliers, and consumers that not only works best in a region but also organically generates a region of capabilities. But the realities are more complex. Do we have regions on a global platform and whose regions? What types of global platform the role regions occupy? These are some of the pertinent questions this article sought to answer.